2011
DOI: 10.3945/ajcn.110.010272
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-hydroxyvitamin D concentrations in relation to cardiometabolic risk factors and metabolic syndrome in postmenopausal women

Abstract: Higher serum 25(OH)D concentrations may be inversely associated with adiposity, triglycerides, triglyceride:HDL-cholesterol ratio, and metabolic syndrome but are not associated with LDL and HDL cholesterol, insulin, glucose, HOMA-IR, or HOMA-β in postmenopausal women. This trial was registered at clinicaltrials.gov as NCT00000611.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
71
1
8

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(92 citation statements)
references
References 68 publications
12
71
1
8
Order By: Relevance
“…Similar inverse associations between serum 25(OH)D levels and triglycerides were also documented by other studies [33,34]. The potential biological mechanism underlying this relation is still not completely understood but may be mediated, in part, by the effects of dietary calcium [35]. Higher serum 25(OH)D concentrations increase the absorption of intestinal calcium, which may bind to fatty and bile acids and form insoluble lipid-calcium complexes, thereby inhibiting the absorption of cholesterol and increasing fecal excretion [36].…”
Section: Discussionsupporting
confidence: 82%
“…Similar inverse associations between serum 25(OH)D levels and triglycerides were also documented by other studies [33,34]. The potential biological mechanism underlying this relation is still not completely understood but may be mediated, in part, by the effects of dietary calcium [35]. Higher serum 25(OH)D concentrations increase the absorption of intestinal calcium, which may bind to fatty and bile acids and form insoluble lipid-calcium complexes, thereby inhibiting the absorption of cholesterol and increasing fecal excretion [36].…”
Section: Discussionsupporting
confidence: 82%
“…Also in children, the association between vitamin D and cardiac morbidity seems to be present -as seen in the NHANES study where vitamin D deficiency was associated with hypertension, low HDL-cholesterol levels and elevated PTH levels (39). Another possible cardio-protective effect of vitamin D may be via lipid regulation, as the association between vitamin D deficiency and a less favourable lipid profile has been reported earlier (1,2,11,13,41). The positive correlation between 25(OH)D and HDL in postmenopausal women also seen in DOPS has previously been investigated and the subclass of large HDL was accounting for the difference (42).…”
Section: Discussionmentioning
confidence: 85%
“…The theory of a relationship between vitamin D and cardiovascular disease (CVD) and mortality is not new (2,3,4,5,6,7,8). The main dispute remains whether vitamin D is just a marker for a worse prognosis (9,10) potentially explained by other factors, as vitamin D deficiency has also been associated with obesity (1, 2, 11), smoking (2), ageing (1,12,13) and less physical activity (2,11). Though the major source of vitamin D is dermal production triggered by the sun (3,14), vitamin D is also ingested and could thus be a marker of general diet composition.…”
Section: Introductionmentioning
confidence: 99%
“…However, data regarding the association between vitamin D and insulin resistance (IR), a recognized precursor of type 2 diabetes, have not been entirely consistent. Most observational studies [5][6][7][8][9][10][11][12][13][14][15] showed a favorable association of circulating 25-hydroxyvitamin D (25(OH)D), a commonly used biomarker for the assessment of systemic vitamin D status, with the homeostasis model assessment of IR (HOMA-IR), whereas some others [16][17][18][19] could not find such an association in non-diabetic individuals. Besides, clinical trials have reported mixed results regarding the effect of vitamin D supplementation on IR 3,4 .…”
Section: Introductionmentioning
confidence: 99%